Influencing the environmental factors on the abundance of puerulus Panulirus homarus in the Mentawai Islands, West Sumatra, Indonesia - SUPARNO SUPARNO; YUSRA YUSRA; AMELIA SRIWAHYUNI LUBIS; AIDY FITRI YUSEN VIZA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Suparno, Yusra, Lubis AS, Viza AFY. 2024. Influencing the environmental factors on the abundance of puerulus Panulirus homarus in the Mentawai Islands, West Sumatra, Indonesia. Biodiversitas 25: 3758-3767. The lobster puerulus, the final larval stage of the spiny lobster, is significantly influenced by environmental factors, making it crucial for sustainable aquaculture development. This study aimed to analyze how these factors affect the abundance of puerulus Panulirus homarus (Linnaeus, 1758) in the Mentawai Islands, West Sumatra, Indonesia has practical implications for aquaculture. A one-way analysis of variance revealed that the temporal period significantly impacts the abundance of puerulus P. homarus (P<0.05). In February (west season), the abundance was not significantly different from April (transition season I), but both differed significantly from June (east season). The highest abundance occurred in June (33.8±4.21 ind/trip), followed by April (27.00±5.00 ind/trip) and February (23.20±2.22 ind/trip). Regression analysis showed that temperature (R²=0.8111), salinity (R²=0.5158), and phosphate (R²=0.5492) strongly correlated with puerulus abundance. In contrast, chlorophyll-a (R²=0.2236), nitrate (R²=0.4136), and sea current velocity (R²=0.0223) were less significant. These results emphasize the importance of temperature, salinity, and phosphate as key factors influencing puerulus distribution, providing valuable insights for sustainable aquaculture. Environmental parameters were observed using Aqua Modis satellite imagery. They included Sea Surface Temperature (SST), chlorophyll-a concentration, and current velocity, showing a good correlation with field measurements from the Copernicus Marine Environment Monitoring Service (CMEMs).